Yvonne A. Owuor Artist Lecture: Imagination, Thesholds and Ennui: Summons to Alt. Decoloniality? (Conference Modalities 2021, 2021)
As part of its international online conference "Africa*n Relations: Modalities Reflected" that took place from 14 to 17 July 2021 the Cluster of Excellence presented Nairobian creative writer Yvonne A. Owuor with a lecture on "Imagination, Thesholds and Ennui: Summons to Alt. Decoloniality?". She was introduced by Joschka Philipps, Junior Research Group Leader at the Cluster of Excellence. For more information: https://www.africamultiple.uni-bayreuth.de/en/news/2021/2021-08-05_conference_report/index.html